The short-term and long-term results of three-stage surgical treatment of ulcerative colitis with formation of ileal J-pouch - P. V. Tsarkov; A. Yu. Kravchenko; I. A. Tulina; Yury Ye. Kitsenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2016)
Aim of investigation. To estimate results of three- stage treatment approach in severe ulcerative colitis aimed for resection of affected colon and restoration of intestinal continuity. Material and methods. Overall 22 patients were treated according to the three-stage mode, of them 20 were operated urgently due to development of acute complications. The average duration of conservative treatment was 32,8±42,5 months. All patients at the first stage underwent operations related to the emergency state, at the second stage - reconstructive surgery with formation of the ileal J-pouch followed by closure of ileostoma. Results. Patients, who underwent the first stage of treatment on the basis of our institution, had shorter time of surgical treatment, as compared to the cases when colectomy was performed in the other clinics: 4,7±1,6 and 46,1±39,8 months respectively (p=0,02). The average work capacity recovery after surgical treatment was 4±2 months. Stool frequency was 6,1±2,45 times per day, every fifth patient had nighttime defecation; 19 of 21 patients could distinguish type of their reservoir contents and were able to provide its retention. Pouchitis was observed in 21% of cases. The pouch malfunction requiring its resection occurred in 4%. Conclusions. The three-stage surgery for ulcerative colitis is an optimum management approach in the presence of complicated ulcerative colitis. It allows to carry out colonic resection with the lowest risk of morbidity, to create the intestinal reservoir , to provide social professional rehabilitation of patients and to reduce postoperative complications rate significantly. Key words: ulcerative colitis, ileal pouch, colectomy, proctectomy, laparoscopy